Ephemeral territories : representing nation, home, and identity in Canada - Manning, Erin (University of Minnesota Press, 2003)
Ephemeral Territories weaves together narratives and representations of Canadian identity--from political philosophy and cultural theory to art and films--to develop and complicate familiar views of identity and selfhood. In a critical engagement with notions of territory, identity, racial difference, separatism, multiculturalism, and homelessness, Manning delves into the question of what it means to be at home in Canada.